Association of weekend admission and clinical outcomes in hospitalized patients with sepsis: An observational study. Issue 26 (26th June 2020) - Bernet, Selina; Gut, Lara; Baechli, Ciril; Koch, Daniel; Wagner, Ulrich; Mueller, Beat; Schuetz, Philipp; Kutz, Alexander
Abstract : Abstract: Sepsis is associated with impaired clinical outcomes. It requires timely diagnosis and urgent therapeutic management. Because staffing during after-hours is limited, we explored whether after-hour admissions are associated with worse clinical outcomes in patients with sepsis. In this retrospective cohort study, we analyzed nationwide acute care admissions for a main diagnosis of sepsis in Switzerland between 2006 and 2016 using prospective administrative data. The primary outcome was in-hospital mortality using multivariable logistic regression models. Secondary outcomes were intensive care unit (ICU) admission, intubation, and 30-day readmission. We included 86, 597 hospitalizations for sepsis, 60.1% admitted during routine-hours, 16.8% on weekends and 23.1% during night shift. Compared to routine-hours, we found a higher odds ratio (OR) for in-hospital mortality in patients admitted on weekends (Adjusted OR 1.05, 95% confidence interval [95% CI] 1.01, 1.10, P = .041). Also, the OR for ICU admission (OR 1.14, 95% CI 1.10, 1.19, P < .001) and intubation (OR 1.18, 95% CI 1.12, 1.25 P < .001) was higher for weekends compared to routine-hours. Regarding 30-day readmission, evidence for an association could not be observed. Night shift admission, compared to routine-hours, was associated with a higher OR for ICU admission and intubation (ICU admission: OR 1.28 (1.23, 1.32), P < .001; intubation: OR 1.31, 95% CI 1.25, 1.37, P < .001) but with a lower OR for in-hospital mortality (OR 0.93, 19% CI 0.89, 0.97, P = .001). Among hospitalizations with a main diagnosis of sepsis, weekend admissions were associated with higher OR for in-hospital mortality, ICU admission, and intubation. Whether these findings can be explained by staffing-level differences needs to be addressed. Abstract : Supplemental Digital Content is available in the text